Digitoids: a novel computational platform for mimicking oxygen-dependent firing of neurons in vitro - Rachele Fabbri; Rachele Fabbri; Ermes Botte; Ermes Botte; Ermes Botte; Arti Ahluwalia; Arti Ahluwalia; Arti Ahluwalia; Chiara Magliaro; Chiara Magliaro; Chiara Magliaro (Frontiers in Neuroinformatics, 2025)
IntroductionComputational models are valuable tools for understanding and studying a wide range of characteristics and mechanisms of the brain. Furthermore, they can also be exploited to explore biological neural networks from neuronal cultures. However, few of the current in silico approaches consider the energetic demand of neurons to sustain their electrophysiological functions, specifically their well-known oxygen-dependent firing.MethodsIn this work, we introduce Digitoids, a computational platform which integrates a Hodgkin-Huxley-like model to describe the time-dependent oscillations of the neuronal membrane potential with oxygen dynamics in the culture environment. In Digitoids, neurons are connected to each other according to Small-World topologies observed in cell cultures, and oxygen consumption by cells is modeled as limited by diffusion through the culture medium. The oxygen consumed is used to fuel their basal metabolism and the activity of Na+-K+-ATP membrane pumps, thus it modulates neuronal firing.ResultsOur simulations show that the characteristics of neuronal firing predicted throughout the network are related to oxygen availability. In addition, the average firing rate predicted by Digitoids is statistically similar to that measured in neuronal networks in vitro, further proving the relevance of this platform.DicussionDigitoids paves the way for a new generation of in silico models of neuronal networks, establishing the oxygen dependence of electrophysiological dynamics as a fundamental requirement to improve their physiological relevance.